BRIDGING THE GAP - febbyriane, shanna talita; Febrianto, Aziza Restu (Jurnal Bahasa Lingua Scientia, 2025)
The research explores how Indonesian hotel staff perceive their needs of acquiring English competence and explores the communication challenges they face. As global guest expectations rise, English proficiency becomes essential for hotel employees to deliver high-quality service. Employing a qualitative narrative inquiry approach, the research investigates the experiences of six hotel staff members from diverse job roles through in-depth interviews. Findings reveal that English is used situationally, primarily with foreign guests, and that speaking and listening are the most challenging skills due to limited vocabulary, unfamiliar accents, and lack of real-world practice. While some staff benefit from workplace training and AI tools like ChatGPT, disparities in digital access and confidence persist. The study highlights the importance of English for Specific Purposes (ESP) instruction and the potential of blended learning approaches that combine AI tools with traditional, face-to-face training. The study suggests recommendations that include implementing role-specific ESP programs, enhancing practical exposure, and addressing technological gaps to support inclusive and effective language development in the hospitality sector.